Kajian Geografis dan Strategi Pengembangan Berbasis SWOT dalam Optimasi Objek Wisata Alam Tilangnga’ Kabupaten Tana Toraja - Anggreani, Indri; Rifani, Irfan; Ramadhan, Muhamad Isa; Putri, Anindya Puspita; Kumaat, Jocye Christian; Suoth, Grace Feibe Evangelista (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
This research aims to analyze the geographical study of the Tilangnga' Natural Tourism Object in Tana Toraja Regency using a quantitative descriptive approach and SWOT analysis. Data was collected over three months through observation, interviews, documentation, and literature review, with variables covering physical and non-physical geography. The results indicate that physical aspects include paved road access (strength), a location close to the city center (opportunity), and cool temperatures due to surrounding vegetation. Non-physical aspects include local traditions related to ancient eels (strength), scattered trash (threat), and limited facilities and parking space (weakness). Based on the weighting of ALI (1.2) and ALE (1.6), the tourism object is in quadrant 1, indicating potential to leverage strengths to seize opportunities. The recommended priority strategy is aggressive (growth-oriented strategy), such as optimizing facilities, waste management, and promoting local uniqueness. This research emphasizes the importance of integrating physical and socio-cultural geographical aspects in sustainable tourism development.